How practical is the application of percutaneous nephrolithotomy scoring systems? Prospective study comparing Guy’s Stone Score, S.T.O.N.E. score and the Clinical Research Office of the Endourological Society (CROES) nomogram - Anurag Singla (Taylor & Francis Group, 2017)
Objective: To prospectively compare the Guy’s Stone Score (GSS), S.T.O.N.E. [stone size (S), tract length (T), obstruction (O), number of involved calices (N), and essence or stone density (E)] score and the Clinical Research Office of the Endourological Society (CROES) nephrolithometric nomogram to predict percutaneous nephrolithotomy (PCNL) success rate and assess the correlation with perioperative complications. Patients and methods: We prospectively evaluated all consecutive PCNL patients at our institute between 1 November 2013 and 31 May 2015. The above scoring systems were applied to preoperative non-contrast computed tomography and the practical difficulties in such applications were noted. Perioperative complications and the stone-free rate (SFR) were also recorded. Receiver operating characteristic curves were drawn and the areas under curves were compared and appropriate statistical analysis done. Results: In all, 48 renal units were included in the study. The overall SFR was 62.2%. The presence of staghorn stones (β = 27.285, 95% confidence interval 1.19–625.35; P = 0.039) was the only significant variable associated with the residual stones on multivariate analysis. Stone-free patients had significantly lower median GSS (2 vs 4) and S.T.O.N.E. scores (6 vs 10) and higher median CROES scores (83% vs 63%) (all P < 0.001) compared to residual-stone patients. All scoring systems were significantly associated with SFR (all P < 0.001). There was no significant difference in the areas under curves of the scoring systems (0.858, 0.923, and 0.931, respectively). Furthermore, all scoring systems had weak correlations with Clavien–Dindo classified complications (r = 0.29, P = 0.045; r = 0.40, P = 0.005 and r = −0.295, P = 0.04, respectively). We found no standardisation for the measurement of stone dimensions, tract length, Hounsfield units, and staghorn definition. Conclusions: All scoring systems equally predicted SFR and had a weak correlation with Clavien–Dindo complications. Standardisation is needed for the variables in which they have been found deficient.